Turn! Turn! Turn!: A time for engaged learning. The engagement of scholarship and practice in a classroom setting. (March 2016) - Knassmüller, Monika
As the integration of academic teaching and research with communities of practice is considered a major concern of public administration since its founding as a field, professional programmes were established on the premise that there is a positive relationship between practice and scholarship. However, the balance between them is considered delicate as they differ in the context, processes and purposes of their practices. The respective members not only use different vocabularies but base their professional action and reasoning on different logics. This paper develops the idea that part-time professional programmes might be conceptualized as a separate (temporary) system with a distinct frame of reference and language that is governed by its own logic but linked to the two other systems of scholarship and practice. The practical consequences of this approach are explored with regard to the role and objectives of research in professional programmes and the difficulties to achieve them.